Music and Time Perception in Audiovisuals: Arousing Soundtracks Lead to Time Overestimation No Matter Their Emotional Valence - Alessandro Ansani (MDPI AG, 2021)
One of the most tangible effects of music is its ability to alter our perception of time. Research on waiting times and time estimation of musical excerpts has attested its veritable effects. Nevertheless, there exist contrasting results regarding several musical features’ influence on time perception. When considering emotional valence and arousal, there is some evidence that positive affect music fosters time underestimation, whereas negative affect music leads to overestimation. Instead, contrasting results exist with regard to arousal. Furthermore, to the best of our knowledge, a systematic investigation has not yet been conducted within the audiovisual domain, wherein music might improve the interaction between the user and the audiovisual media by shaping the recipients’ time perception. Through the current between-subjects online experiment (n = 565), we sought to analyze the influence that four soundtracks (happy, relaxing, sad, scary), differing in valence and arousal, exerted on the time estimation of a short movie, as compared to a no-music condition. The results reveal that (1) the mere presence of music led to time overestimation as opposed to the absence of music, (2) the soundtracks that were perceived as more arousing (i.e., happy and scary) led to time overestimation. The findings are discussed in terms of psychological and phenomenological models of time perception.